Cyclodextrin- and calixarene-based polycationic amphiphiles as gene delivery systems: a structure–activity relationship study. Issue 6 (4th December 2014) - Gallego-Yerga, Laura; Lomazzi, Michela; Franceschi, Valentina; Sansone, Francesco; Ortiz Mellet, Carmen; Donofrio, Gaetano; Casnati, Alessandro; García Fernández, José M.
Abstract : Multi-head/multi-tail facial amphiphiles built on cyclodextrin (CD) and calixarene (CA) scaffolds are paradigmatic examples of monodisperse gene delivery systems. Abstract : Multi-head/multi-tail facial amphiphiles built on cyclodextrin (CD) and calixarene (CA) scaffolds are paradigmatic examples of monodisperse gene delivery systems. The possibility to precisely control the architectural features at the molecular level offers unprecedented opportunities for conducting structure–activity relationship studies. A major requirement for those channels is the design of a sufficiently diverse ensemble of compounds for parallel evaluation of their capabilities to condense DNA into transfection nanoparticles where the gene material is protected from the environment. Here we have undertaken the preparation of an oriented library of β-cyclodextrin (βCD) and calix[4]arene (CA4 ) vectors with facial amphiphilic character designed to ascertain the effect of the cationic head nature (aminothiourea-, arginine- or guanidine-type groups) and the macrocyclic platform on the abilities to complex plasmid DNA (pDNA) and in the efficiency of the resulting nanocomplexes to transfect cells in vitro . The hydrophobic domain, formed by hexanoyl or hexyl chains, remains constant in each series, matching the overall structure found to be optimal in previous studies. DLS, TEM and AFM data support that all the compounds self-assemble in the presence of pDNA through a process that involves initially electrostatic interactions followed by formation of βCD or CA4 bilayers between the oligonucleotide filaments. Spherical transfectious nanoparticles that are monomolecular in DNA are thus obtained. Evaluation in epithelial COS-7 and human rhabdomyosarcoma RD-4 cells evidenced the importance of having primary amino groups in the vector to warrant high levels of transfection, probably because of their buffering capacity. The results indicate that the optimal cationic head depends on the macrocyclic core, aminothiourea groups being preferred in the βCD series and arginine groups in the CA4 series. Whereas the transfection efficiency relationships remain essentially unchanged within each series, irrespective of the cell type, the optimal platform (βD or CA4 ) strongly depends on the cell type. The results illustrate the potential of monodisperse vector prototypes and diversity-oriented strategies on identifying the optimal candidates for gene therapy applications.